Audience Reception Analysis Of Tolerance In The 'Login' Program Episode '6 Religious Leaders' On Deddy Corbuzier’s Youtube Channel - Fajar Muharam; Abi Fajar Ramadhan; Haryo Windratno; Ferrari Lancia (Jurnal Ilmiah Multidisiplin, 2025)
Advances in technology and information have clearly manifested with the emergence of various new media platforms that are widely utilized. One such platform is the social media platform YouTube, which is used for information dissemination. This is exemplified by the program "Login" on Deddy Corbuzier’s YouTube, which features discussions on interfaith topics aimed at enhancing understanding and tolerance among religious communities in Indonesia through social media and digital platforms. This research aims to analyze audience reception about tolerance in one of the "Login" program episodes titled "6 Religious Leaders" on Deddy Corbuzier's YouTube channel. The method employed is reception analysis using a qualitative approach, guided by Stuart Hall's reception theory, which divides audience interpretation of media messages into three positions: dominant, negotiated, and oppositional. Broadly speaking, the research findings indicate that all audience members occupy the dominant position, where they fully adopt and accept the meanings constructed by the message creators. This aligns with the predominant thoughts and views of the message creators. There is one audience member in the negotiated position, while no audience members were found in the oppositional position.